The Role of Information and Communication Technology in Enhancing Community Participation in Government Decision-Making Processes: A Case Study in Surabaya City - Edrion Tama (Generasi Sains Indonesia, 2024)
This study aims to examine the impact of Information and Communication Technology (ICT) on enhancing community participation in government decision-making processes in Surabaya City. A quantitative approach was employed, utilizing a survey method with a sample of 500 respondents selected through random sampling from various neighborhoods in the city. Descriptive and inferential statistical analyses were used to analyze the data. The results indicate that the use of ICT significantly increases community participation in government decision-making. Approximately 80% of respondents reported easier access to government information through official websites and applications. Moreover, about 75% of respondents stated that ICT enables them to provide direct feedback and opinions to the government, enhancing transparency and accountability in decision-making processes. However, around 20% of respondents still face challenges in accessing technology and lack digital literacy. Therefore, efforts are needed to improve accessibility and understanding of technology among the community to achieve broader and more equitable participation.